A study on the internet usage among the diploma students in UiTM Samarahan Campus. case study: University Technology Mara Sarawak/ Etherianna Lemai, Madelina Joseph & Wenny Jerom - Lemai, Etherianna; Joseph, Madelina; Jerom, Wenny (2004)
This study is to investigate, analyze and identify the Internet usage among the diploma students in UiTM Samarahan Campus. Here, a study is conducted to see how the students manage to use the Internet facilities that had been provided in the campus. In the study, various type of methods are use to collect the accurate data and information that are required by the researcher of the study. These methods include distribution of questionnaire, interview, observation and the use of retrieving information via Internet. In addition to the study, 120 students had been selected as a sample. They are required to fill in the questionnaires. The success of this study is base on their responses. However, out of the 120 questionnaires distributed, only 110 questionnaires are return back to researcher.